A COMPREHENSIVE OVERVIEW ON THE EMERGING TECHNOLOGIES FOR RAPID DETECTION AND PREVENTION OF FOOD POISONING CASES - 1ALI HADI HUSSAIN AL SHARYAH, 2FAHAD HADI AL SHARYAH, 3ABDULLAH HADI BAN HSAEEN AL SHARYAH, 4HAMAD HADI ALMUHAMIDH, 5MOHAMMED SAEED MOHAMMED AL JARAH, 6HADI MANA HUSSAIN AL SHARYAH, 7MARZOUQ MOHAMMED HUSSAIN ALYAMI, 8MAHADI MANE HUSSIEN ALSHARIYAH, (Chelonian Research Foundation, 2022)
Foodborne infections undermine worldwide well-being, causing numerous deaths and illnesses each year. Fast discovery and prevention of nourishment harming are essential to decreasing the open well-being and financial impacts of nourishment harming. Modern innovation holds the guarantee of rapidly fathoming the distinguishing proof of foodborne sicknesses and anticipating defilement all through the nourishment supply. This comprehensive survey covers various innovations, counting blockchain, genome sequencing, quick symptomatic packs, nanotechnology, and more, and clarifies their applications in nutrition security. It, too, examines the challenges and prospects of joining these advances to combat irresistible diseases successfully. Keywords: food safety, foodborne illnesses, emerging technologies, rapid detection, prevention, blockchain, genomic sequencing, pathogen identification, nanotechnology, IoT, artificial intelligence.